Anti-Inflammatory Effects of BoNT/A Against Complete Freund’s Adjuvant-Induced Arthritis Pain in Rats: Transcriptome Analysis - Li, Xinhe; Ye, Yinshuang; Zhou, Wenwen; Shi, Qilin; Wang, Lin; Li, Tieshan (Frontiers in Pharmacology, 2021)
Arthritis is the most common cause to lead to chronic pain. Botulinum toxin type A (BoNT/A) has been widely used to treat chronic pain. In our previous study, we confirmed the anti-inflammatory and antinociceptive effects of BoNT/A in the Complete Freund's Adjuvant (CFA)-induced arthritis model, but the underlying anti-inflammatory mechanism was not fully elucidated. The purpose of this study was to investigate the anti-inflammatory effects and mechanisms of BoNT/A on arthritis using transcriptomic analysis. The BoNT/A was injected into the rat ankle joint on day 21 after CFA injection. The Von Frey and hot plate tests were applied to assess the pain-related behaviors at different time points. Five days after BoNT/A treatment, gene expression profiling in dorsal root ganglion (DRG) was performed using RNA sequencing (RNA-seq). The differentially expressed genes (DEGs) were analyzed by various tools. The mechanical allodynia and thermal hyperalgesia were signiﬁcantly reversed after BoNT/A injection. RNA-seq revealed 97 DEGs between the CFA group and Sham group, these DEGs were enriched inflammatory response and IL-17 signaling pathway, etc. There are 71 DEGs between the CFA+BoNT/A group and CFA group, these DEGs related to response to peptide, PI3K-Akt signaling pathway and ECM-receptor interactions, etc. Three key genes were significantly decreased after CFA-induced arthritis pain, while BoNT/A increased the expression of these genes. The anti-inflammatory mechanisms of BoNT/A against CFA-induced arthritis pain might be associated with PI3K-Akt signaling pathway and so on. Moreover, S100A9, S100A8 and MMP8 genes might be potential biomarkers of CFA-induced arthritis pain in rats, as well as pharmacological targets of BoNT/A.